Return On Asset, Audit Quality and Accrual Earning Management Practice of LQ 45 Companies Listed in IDX - Murtianingsih Aning (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Malang, 2021)
This study aims to analyze and test the effect of the variable Return On Asset and Audit Quality on earnings management practices at LQ 45 companies listed on the Indonesia Stock Exchange in the 2016-2018 period. The population consists of the LQ 45 companies listed on the Indonesia Stock Exchange. The researchers took the sample with the purposive sampling technique and resulted in 33 companies. The audit quality used is the auditor in the rank the big-four. The type of research is associative causal with quantitative data and secondary data using descriptive statistical analysis, classic assumption techniques, multiple regression analysis, coefficient of determination (R²), and t-test hypothesis. The research result stated that Return on asset dan audit quality has an effect positive and significantly on earnings management practice. An interesting research finding is that the managers of LQ 45 companies tend to do little accrual earnings management.